Impacts of Canada's minimum age for tobacco sales (MATS) laws on youth smoking behaviour, 2000–2014. Issue Volume 27:Issue e2(2018) (13th January 2018) - Callaghan, Russell Clarence; Sanches, Marcos; Gatley, Jodi; Cunningham, James K; Chaiton, Michael Oliver; Schwartz, Robert; Bondy, Susan; Benny, Claire
Abstract : Background: Recently, the US Institute of Medicine has proposed that raising the minimum age for tobacco purchasing/sales to 21 years would likely lead to reductions in smoking behavior among young people. Surprisingly few studies, however, have assessed the potential impacts of minimum-age tobacco restrictions on youth smoking. Objective: To estimate the impacts of Canadian minimum age for tobacco sales (MATS) laws on youth smoking behaviour. Design: A regression-discontinuity design, using seven merged cycles of the Canadian Community Health Survey, 2000–2014. Participants: Survey respondents aged 14–22 years (n=98 320). Exposure: Current Canadian MATS laws are 18 years in Alberta, Saskatchewan, Manitoba, Quebec, the Yukon and Northwest Territories, and 19 years of age in the rest of the country. Main outcomes: Current, occasional and daily smoking status; smoking frequency and intensity; and average monthly cigarette consumption. Results: In comparison to age groups slightly younger than the MATS, those just older had significant and abrupt increases immediately after the MATS in the prevalence of current smokers (absolute increase: 2.71%; 95% CI 0.70% to 4.80%; P=0.009) and daily smokers (absolute increase: 2.43%; 95% CI 0.74% to 4.12%; P=0.005). Average past-month cigarette consumption within age groups increased immediately following the MATS by 18% (95% CI 3% to 39%; P=0.02). There was no evidence of significant increases in smoking intensity for daily or occasional smokers after release from MATS restrictions. Conclusion: The study provides relevant evidence supporting the effectiveness of Canadian MATS laws for limiting smoking among tobacco-restricted youth.